Gaps and opportunities for the integrated delivery of mother-child care, postpartum family planning and nutrition services in Burkina Faso, Côte d'Ivoire and Niger - Halima Tougri; Maurice E. Yameogo; Rachidatou Compaoré; Désiré Dahourou; Danielle Y. Belemsaga; Bertrand Meda; Denise Kpebo; Marguerite Ndour; Seni Kouanda (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Maternal and infant deaths can be prevented through integrated service delivery during pregnancy, postpartum, and early childhood. Our study analyses the gaps and opportunities associated with integrating maternal, newborn, and child health (MNCH) services with postpartum family planning (PPFP) and nutrition services at different points of contact in health facilities in a preintervention context in west Africa. # Methods We conducted a qualitative study from June to July 2018 in Burkina Faso, Côte d'Ivoire and Niger. The points of contact studied at the health facility level were the prenatal care, postpartum care and immunisation/growth monitoring services. Individual in-depth interviews were used to collect data from key informants (providers, community health workers and mother-child health programme managers). To measure the degree of service integration, we used the dimensions and indicators included in the Integra Initiative framework concerning four aspects of integration: physical (the availability of multiple services in the health facility), temporal (the availability of care more than one day per week), provider level, and functional (the receipt of integrated services by the client). # Results The findings of this study show that the integrated delivery of MNCH, PPFP, and nutrition services is configured in similar ways in Burkina Faso, Côte d'Ivoire and Niger and is insufficient at all points of contact. Physical integration is high. However, the study found important gaps in temporal, functional and provider-level integration. The main barriers to integrated service delivery are the shortage of providers, the lack of training in integrated service delivery, and insufficient service organisation. However, the availability of multiple services throughout the week, the multiple points of contact between the mother-child pair and the health system, and the multiple skills of providers represent opportunities for functional integration through the establishment of a formal referral system between the different care units with follow-up and feedback among service providers. # Conclusions The provision of training and the development of a well-organised referral system in different health facilities, taking into account the specific characteristics of each health facility (urban/rural, primary health facility/district hospital), can improve the delivery of integrated MNCH, PPFP, and nutrition care to the mother-child pair.